Hacking the City: disability and Access in Cities Made of Software - Cake, D.; Kent, Michael (Springer, 2014)
Citizens with impairments manage a disabling environment of barriers, borders, walls, steps and inconvenience. Yet there have been transformations of buildings, roads and signs after decades of activism. Cake and Kent investigate how this analogue history applies to digital environments. The imperative for universal design – being aware of the multiple uses and literacies that approach any product of environment – is crucial when enabling a digital city.